Intrinsic and extrinsic attributes, attitude towards seaweed crackers and purchase intention of seaweed crackers products developed by School of Food Science and Nutrition, Universiti Malaysia Sabah - Christine Julius (2012)
Seaweed can be a very attractive natural source of new compounds with biological activity. In view of that, School of Food Science and Nutrition produced Seaweed Crackers for research purposes. The objectives of this study were to examine the consumers' perception based on intrinsic and extrinsic attributes and purchase intention towards seaweed crackers product at various schools and department in Universiti Malaysia Sabah. The study also examines the mediating effect of attitude towards seaweed crackers attributes on the relationship between intrinsic and extrinsic attributes and purchase intention. 134 respondents were used for the statistical analysis of which collected from different schools and departments in Universiti Malaysia Sabah using purposive sampling method. The results show that ingredients and price have a significant influence on purchase intention while other attributes such as brand name, texture, packaging, and ingredients have significant with attitude towards seaweed crackers attributes only. The regression analysis results show that attitude towards seaweed crackers attributes fully mediates the relationships of purchase intention and partially mediates the relationship with ingredients attributes. Based on the findings, only ingredients attribute found to significantly influence to both attitude towards seaweed crackers attributes and purchase intention. Price attributes has significant effect on purchase intention and insignificant effect on attitude. Other attributes namely brand name, packaging, and texture have significant effect on attitude towards seaweed crackers attributes, however, insignificant effect on purchase intention. Both colour and artificial flavour have no significant to attitude towards seaweed crackers attributes and purchase intention. The results suggest that manufacturers or researchers should focus on ingredients attributes in order to meet their consumers' expectation. This study also included the limitation of the study and recommendation for future researchers.